ANALYSIS OF PROBLEM AND NEED ON THE AFFECTIVE ASSESMENT IMPLEMENTATION FOR LEARNERS IN MADRASAH ALIYAH - Nurul Imtihan; Ahyar Ahyar (Universitas Muhammadiyah Semarang, 2018)
This paper aims to report various issues related to affective domain assessment in an effort tounderstand the needs of teachers in implementing affective assessment in Madrasah Aliyah. Data collection isdone through interview technique and focus group discussion (FGD). The collected data were analyzedinductively to produce meaningful information points. Predicate as a public school characteristic of Islamicreligion attached to Madrasah Aliyah institution has implications to the demands of realizing the character ofmorality or morals as a value of excellence for learners. Implementation of education system in Madrasah Aliyahwhich has been accused still has weaknesses require real efforts to improve its quality. The development ofvalue-based affective assesment instruments combined with the scale of religiosity is representative to expressand recognize the disposition of learners’s affective characteristics more broadly and fundamentally for theinterest of improving the assessment system in particular and improving the quality of education in general. Kata Kunci : development of assessment instruments, domain afektif, focus group discussion, madrasah aliyah.